Welfare states, labour market institutions and the working poor: a comparative analysis of 20 European countries - Henning Lohmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
This paper regards the incidence of in-work poverty and how it is reduced by the payment of social transfers in 20 European countries. It combines a micro- and a macro-level perspective in two-level models. The basis for the analysis is micro-data from the EU Statistics on Income and Living Conditions (EU-SILC) 2005 and macro-data from sources such as the OECD and Eurostat. The broad comparative perspective allows for a separation of different institutional influences, namely the influence of the degree of decommodification, defamilisation and bargaining centralisation. In contrast to previous studies on the working poor which have mainly described country differences in in-work poverty, this paper focuses on the question of how such differences can be ex-plained from a broader perspective of poverty research. In general, the results confirm the overall hypothesis that both welfare state measures and labour market institutions have an influence on in-work poverty. By analysing influences on pre-transfer poverty and poverty reduction separately, I show that such factors have varied effects on in-work poverty. While bargaining centralisation proves to be relevant for the distribution of pre-transfer incomes only, the set-up of the social security system in particular im-pacts the extent of poverty reduction.
Keywords: 330; Armut; Arbeiter; Arbeitskräfte; Niedriglohn; Arbeitsmarktflexibilisierung; Sozialtransfer; Sozialstaat; Vergleich; EU-Staaten